Metastatic Spreading of Community Acquired Staphylococcus aureus Bacteraemia. (2nd July 2011) - Fabio, Giovanna; Carrabba, Maria; Mellace, Luca; Hu, Cinzia; Spagnoli, Diego; Cappellini, Maria Domenica
Abstract : A 29-year-old woman presented to the Fondazione IRCCS "Cà Granda" Ospedale Maggiore, a tertiary care university hospital in Milan (Italy), with skin lesions, fever, myalgia, joint pain and swelling, and a one-week history of low back pain. The diagnosis was Staphylococcus aureus ( S. aureus ) bacteraemia spreading to skin, bones, and joints and a lumbosacral epidural abscess L5-S2. Neither initial focus nor predisposing conditions were apparent. The antibiotic therapy was prolonged for six-weeks with the resolution of fever, skin lesions, articular inflammation, and the epidural abscess. Community-acquired S. aureus infections can affect patients without traditional healthcare-associated risk factors, and community acquisition is a risk-factor for the development of complications. Raised awareness of S. aureus bacteraemia, also in patients without healthcare-associated risk factors, is important in the diagnosis, management, and control of this infection, because failure to recognise patients with serious infection and lack of understanding of empirical antimicrobial selection are associated with a high mortality rate in otherwise healthy people.